REPRESENTASI MASKULINITAS PADA IKLAN (ANALISIS SEMIOTIK ROLAND BARTHES PADA IKLAN GUDANG GARAM DAN IKLAN MS GLOW FOR MEN) - Artyasto Jatisidi; Rifqi Al Mutonik; Bintarto Wicaksono (Universitas Tribhuwana Tungga Dewi, 2022)
Media plays an important role in spreading ideas about popular culture because popular culture requires media to distribute ideas. The Gudang Garam “Jungle” advertisement and the Ms Glow for men ad “Akbar Rais, Arif Muhammad, and Verrel Bramasta” are advertisements for cigarettes and facial care products that emphasize masculinity. Both of these advertisements feature urban men in a casual style. Masculinity is a gender-based trait that is attached to men. The mass media, in this case television advertising, apparently also played a role in confirming this view. Based on semiotic analysis using the Roland Barthes model in the ad impressions of Gudang Garam